2017
DOI: 10.1002/ijgo.12394
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of fetal outcomes following the administration of influenza A/H1N1 vaccination during pregnancy

Abstract: The administration of H1N1 vaccines during pregnancy might reduce the risk of stillbirth, a complication associated with H1N1 infection. The quality of evidence was, however, not adequate to reach a definitive conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…However, between 1997 and 2004 only women in the second and third trimesters were advised to be vaccinated for influenza [ 9 , 43 , 44 ] resulting in limited information on exposures and outcomes like SAB in the first trimester [ 7 , 8 , 10 , 11 , 20 , 45 , 46 ]. More recently, studies and systematic reviews investigating pH1N1-containing vaccines have not identified excess risks of adverse events [ 3 , 12 , 13 , 15 , 18 , 40 , 47 49 ]. Overall, evidence to support the safety of influenza vaccine in pregnant women is substantial.…”
Section: Discussionmentioning
confidence: 99%
“…However, between 1997 and 2004 only women in the second and third trimesters were advised to be vaccinated for influenza [ 9 , 43 , 44 ] resulting in limited information on exposures and outcomes like SAB in the first trimester [ 7 , 8 , 10 , 11 , 20 , 45 , 46 ]. More recently, studies and systematic reviews investigating pH1N1-containing vaccines have not identified excess risks of adverse events [ 3 , 12 , 13 , 15 , 18 , 40 , 47 49 ]. Overall, evidence to support the safety of influenza vaccine in pregnant women is substantial.…”
Section: Discussionmentioning
confidence: 99%
“…The rst choice was meropenim because it has the pregnant category B. The patient was immunized by H1N1 vaccine as it is recommended from many studies with safe effects for mom and natal after birth [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it has been established that vaccinating pregnant women is safe, with no evidence demonstrating a link between immunization during pregnancy and adverse outcomes in offspring [159][160][161][162][163][164][165]. Infants born to mothers who were vaccinated against influenza may have a decreased rate of preterm birth, low birthweight, and stillborn birth, although establishing a causal relationship is challenging [160,[166][167][168][169][170][171]. Infants born to mothers who were severely sick with H1N1 influenza infection have been shown to have an increased risk of preterm birth, decreased 5 min Apgar scores, and an increased risk of death [172][173][174].…”
Section: A Key Role For Maternal Vaccination In Protecting Young Infamentioning
confidence: 99%